Beliefs about emotions: Latent structure and links with emotion regulation and psychopathology - Rodrigo Becerra; Kristin Naragon-Gainey; James J. Gross; Jeneva Ohan; David A. Preece (Journal of Affective Disorders Reports, 2024)
Background: There is evidence that beliefs about emotions are important for mental health. However, this field needs further research. Via the Emotion Beliefs Questionnaire, we aimed to explore the latent structure of emotion beliefs, their associations with numerous emotion constructs, and the role of emotion regulation in mediating emotion beliefs and emotional problems. Methods: This cross-sectional study involved 508 general community adults via an online survey, participants completed the EBQ, the Perth Emotion Regulation Competency Inventory, and the Depression Anxiety Stress Scale-21 for the central analyses, in addition to several related emotion measures. Our analytical strategy included: 1. Factor analyses to test the psychometric properties of the EBQ including its measurement invariance; 2. Correlational analyses to investigate the relationship between beliefs about emotions and several emotion constructs; and 3. Mediation analyses to explore the role of emotion regulation in the association between beliefs about emotions and depression and anxiety. Results: The findings supported a four-factor structure for the EBQ, with invariance across different demographic categories. Beliefs about the controllability of emotions were associated with most emotion constructs relative to beliefs about the usefulness of emotions. The links between beliefs about emotions with depression and anxiety were mediated by emotion regulation. Conclusions: Our findings underscore the importance of assessing the multidimensional emotion beliefs construct, as these beliefs are associated with impaired emotion regulation and many important emotional outcomes. Beliefs about emotion thus represent a useful area for future clinical research so that interventions tackle psychological difficulties in an effective way.